2024
DOI: 10.1002/inmd.20230041
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid drug and delivery techniques for disease therapy: Present situation and future prospect

Tianjiao Wang,
Youhong Tang,
Yuandong Tao
et al.

Abstract: Over the two decades, RNA drugs have gradually made their way from bench to bed. Initially, RNA was not an ideal drug since RNA molecules degrade easily and have a relatively short half‐life in the circulation system. Nevertheless, the chemical modification extended the half‐life of RNA in recent years, which makes RNA drugs a new star in drug discovery industry. RNA molecules hold many properties that facilitate their application as therapeutic drugs. RNAs could fold to form complex conformations to bind to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…miRNAs are closely associated with many significant diseases. The advancement and cost reduction of gene sequencing technologies, along with the development of RNA modification techniques and breakthroughs in delivery systems, have made miRNAs a focal point in disease treatment [ 56 , 57 ]. Employing the miEAA 2.1 analysis platform, we screened DEMs with extensive regulatory effects after SCI and conducted a comprehensive multi-omics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are closely associated with many significant diseases. The advancement and cost reduction of gene sequencing technologies, along with the development of RNA modification techniques and breakthroughs in delivery systems, have made miRNAs a focal point in disease treatment [ 56 , 57 ]. Employing the miEAA 2.1 analysis platform, we screened DEMs with extensive regulatory effects after SCI and conducted a comprehensive multi-omics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study have demonstrated a significant increase in IL-6, TNF-α, and iNOS expression in astrocytes following OGD, with iNOS(+) reactive astrocytes leading to increased neuronal apoptosis (10), suggesting the involvement of A1 astrocytes in post-IS inflammation and oxidative stress. Moreover, it has been found that edaravone inhibits the transformation of A1 astrocytes by suppressing the expression of inflammatory cytokines and chemokines (11). Additionally, astrocytes play a critical role in the redox homeostasis during ischemic stroke, as evidenced by the significantly higher glutathione (GSH) content in astrocytes compared to neurons during OGD, with mitochondrial transfer from astrocytes to neurons aiding in maintaining neuronal mitochondrial function (12).…”
Section: Introductionmentioning
confidence: 99%